Identified, Tracked, and Profiled The Politics of Resisting Facial Recognition Technology - Dauvergne, Peter (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Revealing the politics underlying the rapid globalization of facial recognition technology (FRT), this topical book provides a cutting-edge, critical analysis of the expanding global market for FRT, and the rise of the transnational social movement that opposes it.